Návrh strategie řízení obchodu ve společnosti - Šalomounová, Andrea (Vysoké učení technické v Brně. Fakulta podnikatelská, 2017)
Diplomová práce se zabývá návrhem strategie řízení obchodu ve společnosti. Práce se skládá z popisu podnikání společnosti HORPO, spol. s r. o., analýzy současného stavu maloobchodní jednotky, vyhodnocení teoretických východisek souvisejících s maloobchodní činností a vlastních návrhů řešení včetně podmínek realizace a přínosů těchto návrhů.

This diploma thesis deals with the proposal of a business management strategy in the company. The thesis consists of a description of HORPO´s business, an analysis of the current state of the retail unit, evaluation of the theoretical bases related to retail activities, and in the last part proposals of concrete solutions including the conditions of implementation and benefits of these proposals.
Proposal for Business Management Strategy in the Company
Keywords: maloobchod; retail management; strategie; sortiment; zákazníci; zaměstnanci; SWOT analýza; modernizace; retail store; retail management; strategy; assortment; customers; employees; SWOT analysis; modernization